2021
DOI: 10.1016/j.jamda.2020.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Metformin is Associated with Decreased 30-Day Mortality Among Nursing Home Residents Infected with SARS-CoV2

Abstract: Objectives The COVID-19 pandemic presents an urgent need to investigate whether existing drugs can enhance or even worsen prognosis; metformin, a known mammalian target of rapamycin (m-TOR) inhibitor, has been identified as a potential agent. We sought to evaluate mortality benefit among older persons infected with SARS-CoV-2 who were taking metformin as compared to those who were not. Design Retrospective cohort study Setting and Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 33 publications
5
49
0
Order By: Relevance
“…disease severity. This is in line with recent clinical reports that metformin treatment of diabetic COVID-19 patients resulted in a reduced mortality rate (36)(37)(38). Metformin acts by activating the AMP-activated protein kinase AMPK,(39) which then phosphorylates angiotensin-converting enzyme 2 (ACE2) causing increase in ACE2 expression (40).…”
supporting
confidence: 85%
“…disease severity. This is in line with recent clinical reports that metformin treatment of diabetic COVID-19 patients resulted in a reduced mortality rate (36)(37)(38). Metformin acts by activating the AMP-activated protein kinase AMPK,(39) which then phosphorylates angiotensin-converting enzyme 2 (ACE2) causing increase in ACE2 expression (40).…”
supporting
confidence: 85%
“…The associated benefits of metformin on mortality due to COVID-19 are not restricted to patients with severe disease or hospitalisation. A retrospective analysis in nursing homes demonstrated similar results, showing that residents taking metformin had a significantly reduced 30-day mortality from COVID-19 diagnosis compared to residents without antidiabetic drugs [ 110 ].…”
Section: Antidiabetic Drugsmentioning
confidence: 93%
“…Several studies have shown that insulin therapy was linked to poor prognosis in COVID-19 [ 107 , 108 , 110 ]. However, it is important to underline that the poorer outcomes are probably due to the fact that use of insulin reflects more advanced diabetes and patients who are often older and frailer.…”
Section: Antidiabetic Drugsmentioning
confidence: 99%
“…The included studies were conducted in Austria [14], Belgium [15], China [16][17][18][19][20][21][22][23][24], France [25][26][27], Hong Kong [28], Iraq [29], Italy [30,31], Russia [32]which determines the high relevance of risk factor analysis for outcomes in DM patients to substantiate the strategy for this category of patients. AIM: To assess the effect of clinical and demographic parameters (age, gender, body mass index (BMI, South Korea [33,34], Spain [35,36], UK [37][38][39][40][41] and USA [42][43][44][45].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%